DETERMINASI PEMBENTUKAN SIKAP KONSUMEN PADA MEREK HANDPHONE NOKIA X-PRESS MUSIC DI SURAKARTA - Nugroho, Basuki (Widya Warta, 2009)
Progress in communication industry of mobile phone for adult is greatly influenced by the rapid development of  technonogy in the last decade. Model and menu changes on mobile phone, better known as the handphone, also become a consideration for the producers of handphone. The variables used in this research were brand image, brand confidence of benefits, and advertisement to build consumer attitudes on the mobile phone brand NOKIA X-Press Music in Surakarta. The population of this research was the overall number of objects being researched namely, the buyer and user community of the handphone NOKIA X-Press Music. While, the sampling technique used was the technique of non probability sampling with Convenience sampling method. The sample number is 100 people. The result of regression (F test) showed that there was a significant effect of the independent  variables (brand  image,  brand  benefits and  advertisement  exposure)  as a  whole towards consumer attitudes (F value of 37.511 > F table 2.696). The significance test (test t) of each  independent  variable  towards  consumer  attitudes  showed  that  the  three  independent variables had a significant effect towards consumer attitudes. And, among the three variables, advertisement exposure had the greatest effect towards consumer attitudes.